2016
DOI: 10.1002/mren.201600027
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Polymerization over Metallocene Catalysts Supported on Highly Fibrous Silica Nanoparticles

Abstract: The polymerization of ethylene over a metallocene catalyst supported on amorphous fibrous silica nanoparticles of 250–300 nm in diameter has been investigated. The fibrous silica nanoparticles with large surface area and open pore entrances offer minimal diffusion resistances for the catalyst immobilization onto the silica surface. These fibrous silica particles are synthesized using reverse micelles as a template to grow silica emanating outward as protrusions or platelets from a small silica core. The fibrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Its unique porosity and morphology create good accessibility, allowing for the application of fibrous nano-silica as an interesting inorganic support in catalysis as well as a filler agent in nanocomposite preparation. To the best of our knowledge, only two examples of fibrous silica-supported metallocene catalysts for ethylene polymerization are reported in literature [24,25] . Lee et al [24] employed KCC-1 as a support for a Zr metallocene catalyst in ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its unique porosity and morphology create good accessibility, allowing for the application of fibrous nano-silica as an interesting inorganic support in catalysis as well as a filler agent in nanocomposite preparation. To the best of our knowledge, only two examples of fibrous silica-supported metallocene catalysts for ethylene polymerization are reported in literature [24,25] . Lee et al [24] employed KCC-1 as a support for a Zr metallocene catalyst in ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two examples of fibrous silica-supported metallocene catalysts for ethylene polymerization are reported in literature [24,25] . Lee et al [24] employed KCC-1 as a support for a Zr metallocene catalyst in ethylene polymerization. The authors compared the novel dendrimeric silica nanospheres to industrially applied micronsized silica particles as support and observed an increase in activity from double to triple the activity exhibited by the micron-sized silica system when using KCC-1.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of porous silica have been recently explored for the control of particle morphology and reaction yield improvement. Examples include the mesoporous nanosilicas MCM-41 and SBA-15, amongst other various unique types of silica [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bayal et al [25] reported a tunable synthesis method for DS that allows for control of particle size and textural parameters, while Ernawati et al [26] reported a different TMOS-based tunable synthesis method and studied the effect of synthesis conditions on the morphology of the resulting fibrous silica nanospheres. Concerning the catalytic applications, Lee et al [1] studied purely siliceous DS as support for metallocene catalysts on ethylene polymerization. In this case the authors performed a methylaluminoxane (MAO) pretreatment before the catalyst loading and studied the morphology of the resulting polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Although metallocene catalyst is an effective catalyst, it only shows enhancement of 1-olefins insertion in polymer chain without increasing catalytic activity [6]. In industrial scale, the metallocene catalysts can be used in ethylene polymerization [7], but the polymerization system is more sensitive and it requires large amounts of cocatalyst, such as: methylalumoxane (MAO) [5,8,9]. It is necessary to rely on more suitable catalyst for improving properties of polymer and easy control of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%